DEVOSI KEPADA BUNDA MARIA BERDASARKAN DOKUMEN MARIALIS CULTUS DAN PELAKSANAANNYA DI PAROKI MATER DEI MADIUN - Don Bosco Karnan Ardijanto; Ignatius Damar Putra (Bahasa Indonesia, 2018)
Devotion to Mary is the Church's tradition lived a practiced until today. There are various kinds of devotions to Mary such as: Rosary, Hail Mary, and litany.Besides, there are also many challenges to practice the devotion such as: deification of Mary's figure and magic. In order to guide her people, the Church published Marialis Cultus encyclic. How about opinions of Marialis Cultus encyclic on devotion to Mary? How about understanding of parishioners on content of the Marialis Cultus encyclic? How about practices of devotion to Mary in Mater Dei parish? This study uses qualitative methods. The aim of the study: firstly is to know opinions of Marialis Cultus encyclic on devotion to Mary; Secondly is to grasp understanding of parishioners of Mater Dei Parish on content of the Marialis Cultus and thirdly is to explain their practices of devotion to Mary in Mater Dei Parish. The conclusion of the research shows that most of parishioners never read the Marialis Cultus, but their understanding on devotion to Mary is related to or in line with Marialis Cultus teachings. Just few of their understanding of devotion to Mary is not in line with Marialis Cultus teaching. The research reveals that most of parishioners in Mater Dei Parish devote to Mary personally and incommunity. In the communities, they devote in various manners such as: Rosary recitation, litany, praying “angelus” especially in Mary Month and Rosary Month. In parochial level, most of parishioners say that devotion to Mary is done well but participation of parishioners should be increased. The parishioners alsoconsider that the parish should build a grotto of Mary to increase participation of parishioners in devotion to Mary.